A Diagnostic Approach of Dermatophytic Pseudomycetoma in a Persian Cat - Moraes, Reiner Silveira de; Benevenuto, Luíz Guilherme Dércore; Ferreira, Júlia Franco; Chimenes, Natielly Dias; Ribeiro, Diego; Martins, Robert Pereira; Oliveira, Rodolfo Medrada de; Bartoli, Raphaella Barbosa Meirelles; Dias da Silva, Vera Lucia; Romani, Alana Flávia (Brazilian Journal of Case Reports, 2025)
Dermatophytic pseudomycetoma is an uncommon manifestation of dermatophytosis, which can affect felines, canines, ferrets and humans, with Microsporum canis as the most common causing agent. This report focused on the diagnosis of dermatophytic pseudomycetoma in a Persian cat with alopecia in the nose and tail, in addition to intact and ulcerated subcutaneous nodules that varied from 1 to 3 cm in diameter in the head. The rare infection caused subcutaneous nodules. Diagnosis involved clinical examination, Wood’s lamp, culture, and cytology, suggesting Microsporum canis. This case report underscored the need for a thorough diagnostic approach due to similar clinical presentations in various diseases.